2010
DOI: 10.1523/jneurosci.0834-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Mediated Neuroprotection in a Mouse Model of Human Tauopathy

Abstract: Tau protein in a hyperphosphorylated state makes up the intracellular inclusions of several neurodegenerative diseases, including Alzheimer's disease and cases of frontotemporal dementia. Mutations in Tau cause familial forms of frontotemporal dementia, establishing that dysfunction of tau protein is sufficient to cause neurodegeneration and dementia. Transgenic mice expressing human mutant tau in neurons exhibit the essential features of tauopathies, including neurodegeneration and abundant filaments composed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
109
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(120 citation statements)
references
References 56 publications
11
109
0
Order By: Relevance
“…1A). Despite the early development of tau pathology in P301S‐htau mice, significant neuronal loss has been detected only from 3 months of age (Hampton et al, 2010; Yang et al, 2015). Interestingly, in 2‐month‐old P301S‐htau mice toluidine blue staining of the ventral funiculus (embedded in resin) revealed a marked change in axonal calibre distribution and occasional myelin figures (concentrically layered myelin without axon) suggestive of Wallerian degeneration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Despite the early development of tau pathology in P301S‐htau mice, significant neuronal loss has been detected only from 3 months of age (Hampton et al, 2010; Yang et al, 2015). Interestingly, in 2‐month‐old P301S‐htau mice toluidine blue staining of the ventral funiculus (embedded in resin) revealed a marked change in axonal calibre distribution and occasional myelin figures (concentrically layered myelin without axon) suggestive of Wallerian degeneration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The number of NeuN + dots per square was counted using the cellcounter program (ImageJ software; National Institutes of Health) with a fixed threshold. The cortical layers were defined as follows: layers II and III, 150 μm from the surface to a depth of 350 μm; layer IV, 350-550 μm from the surface; layer V, 550-750 μm from the surface (46). To count Purkinje cells, at least three sagittal sections (6 μm thick) per brain were cut and stained with calbindin antibody.…”
Section: Methodsmentioning
confidence: 99%
“…19 In addition, recent experimental studies with in vitro and mouse models of AD have linked both astrocytes and microglia to neurodegeneration 20 -25 and have shown that activated microglia can lead to hyperphosphorylation and aggregation. 26,27 The idea of reactive glia as a hostile environment for neurons in the context of neurodegeneration has been recently proposed by elegant studies 28,29 on amyotrophic lateral sclerosis and tauopathy mouse models. If this idea proves to apply to AD, an increasing number of reactive glial cells around dense-core plaques might well contribute to their local toxicity by releasing soluble biologically active toxic molecules, such as pro-inflammatory cytokines and reactive oxygen species.…”
Section: Implications For the Role Of Reactive Glial Cells In Admentioning
confidence: 99%